2010
DOI: 10.4414/smw.2010.13070
|View full text |Cite
|
Sign up to set email alerts
|

Trend of burnout among Swiss doctors

Abstract: Burnout levels among Swiss doctors have increased over the last decade, in particular among French-speaking doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 31 publications
7
47
1
5
Order By: Relevance
“…Like in other studies conducted on the population of doctors from primary health care service [25,37], in our investigation the domain of emotional exhaustion was the most prominent among Non-Balint participants. In a study conducted in the Netherlands [38], the percentage of doctors with a high level of emotional exhaustion was smaller compared to our Non-Balint sample (7%:45%), also depersonalization (11%:20%) and for reduced personal accomplishment was almost the same (22%:21.4%) [38].…”
Section: Discussionsupporting
confidence: 68%
“…Like in other studies conducted on the population of doctors from primary health care service [25,37], in our investigation the domain of emotional exhaustion was the most prominent among Non-Balint participants. In a study conducted in the Netherlands [38], the percentage of doctors with a high level of emotional exhaustion was smaller compared to our Non-Balint sample (7%:45%), also depersonalization (11%:20%) and for reduced personal accomplishment was almost the same (22%:21.4%) [38].…”
Section: Discussionsupporting
confidence: 68%
“…We observed a strong rate of burnout (67%) as indicated by high scores for Emotional Exhaustion (EE) and/or depersonalisation (DP) in a questionnaire. This rate is higher than some earlier reported burnout scores ranging from 30% to 45% [12,17]. At an academic faculty, burnout rates around 34% having high scores on EE and/or DP subscales observed by Shanafeld et al [13] are considerable lower than those in our study group.…”
Section: Discussioncontrasting
confidence: 56%
“…A few studies have examined the impact of having children on burnout symptomatology with conflicting results. No relationship was observed between children and burnout in faculty physicians from a department of internal medicine [11] or in a Swiss cross-sectional study of primary care physicians [12], while a study investigating a large number of US surgeons reported that those with children had a significantly lower burnout risk [13].…”
Section: Introductionmentioning
confidence: 99%
“…The worsening of working conditions is also a contributory factor to the increasing burnout rates of doctors. Arigoni et al (2010) found that the burnout level among Swiss doctors has increased throughout the country over the past decade. Overall, general practitioners are considered to be at increased risk of experiencing stress-related suffering compared to other medical specialists.…”
Section: Box 32 Who Global Policy Recommendations On Increasing Accmentioning
confidence: 99%